Presence of lactate dehydrogenase and lactate racemase in Megasphaera elsdenii grown on glucose or lactate. - Hino, T (1993)
Activity of D-lactate dehydrogenase (D-LDH) was shown not only in cell extracts from Megasphaera elsdenii grown on DL-lactate, but also in cell extracts from glucose-grown cells, although glucose-grown cells contained approximately half as much D-LDH as DL-lactate-grown cells. This indicates that the D-LDH of M. elsdenii is a constitutive enzyme. However, lactate racemase (LR) activity was present in DL-lactate-grown cells, but was not detected in glucose-grown cells, suggesting that LR is induced by lactate. Acetate, propionate, and butyrate were produced similarly from both D- and L-lactate, indicating that LR can be induced by both D- and L-lactate. These results suggest that the primary reason for the inability of M. elsdenii to produce propionate from glucose is that cells fermenting glucose do not synthesize LR, which is induced by lactate.